2021
DOI: 10.21203/rs.3.rs-272834/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-respiratory Particles Emitted by Guinea Pigs in Airborne Disease Transmission Experiments

Abstract: Animal models are often used to assess the airborne transmissibility of various pathogens, which are typically assumed to be carried by expiratory droplets emitted directly from the respiratory tract of the infected animal. We recently established that influenza virus is also transmissible via “aerosolized fomites,” micron-scale dust particulates released from virus-contaminated surfaces (Asadi et al., Nature Communications, 2020). Here we expand on this observation, by counting and characterizing the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…The research studies have revealed that the severe acute respiratory syndrome (SARS) epidemic in 2003 and the current global pandemic of coronavirus disease 2019 (COVID-19) predominantly transmitted by contact or through the airborne route. [7][8][9][10] Several preventive strategies such as safe distancing, contact tracing, isolation of the infected person, hand hygiene, and facemasks have been widely employed against the rapid spread of these diseases. [11][12][13][14] Among them, the use of the facemasks have proven to be one of the most effective protective measures against the airborne virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The research studies have revealed that the severe acute respiratory syndrome (SARS) epidemic in 2003 and the current global pandemic of coronavirus disease 2019 (COVID-19) predominantly transmitted by contact or through the airborne route. [7][8][9][10] Several preventive strategies such as safe distancing, contact tracing, isolation of the infected person, hand hygiene, and facemasks have been widely employed against the rapid spread of these diseases. [11][12][13][14] Among them, the use of the facemasks have proven to be one of the most effective protective measures against the airborne virus transmission.…”
Section: Introductionmentioning
confidence: 99%
“…One of the caveats of these measurements in small animals is that detected particles may come from aerosolized fomites, and residual dust generated by movement [43]. In our system, we did not detect any particles originating from dead animals or the environment, but we also saw a noticeable reduction of particles across sizes when movement was minimal, or animals were deeply asleep.…”
Section: Discussionmentioning
confidence: 63%
“…We observed that the reduction in percent of droplets in the 1-10 μm range was more pronounced in females compared to males, and a steeper decline was observed after Delta inoculation compared to Alpha. One of the caveats of these measurements in small animals is that detected particles may come from aerosolized fomites, and residual dust generated by movement [43]. In our system, we did not detect any particles originating from dead animals or the environment, but we also saw a noticeable reduction of particles across sizes when movement was minimal, or animals were deeply asleep.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies using guinea pigs have shown that IAVs are transmissible via aerosolized fomites, microscopic particulates released from virus-contaminated surfaces (such as fur, skin, or bedding) [112], or respiratory droplets [113]. More recently, Asadi et al described some unknown fraction of transmission events between guinea pigs in which aerosolized fomites were thought to be more important than respiratory droplets [114]. Wild bird-origin H5N6 avian influenza virus was also reported to be transmissible in guinea pigs [115].…”
Section: Guinea Pig Modelmentioning
confidence: 99%